Seven-day magic - Eager, Edward; Bodecker, N. M. (New York : Houghton Mifflin Harcourt, 2016)
A seven-day book of magic proves to be fractious for five children, who must learn the book's rules and tame its magic.
Keywords: Magic -- Juvenile fiction; Wishes -- Juvenile fiction; Space and time -- Juvenile fiction; Magic; Wishes; Space and time; Fiction; Juvenile works